AKTIFITAS ANTIOBESITAS EKSTRAK ETANOL JAMBU MAWAR (Syzygium jambos (L.) Alston) PADA TIKUS BETINA GALUR WISTAR - Atun Qowiyyah; Setiadi Ihsan; Renggana Renggana; Maila N. Khoeriyah (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2021)
Obesity prevalence has increased in recent years and has caused severe health problems. This research was carried out to obtain alternative antiobesity therapy with more minimal side effects. The antiobesity activity of rose apple (Syzygium Jambos (L.) Alston) leaves on female Wistar rats induced by high carbohydrate food for 45 days and subcutaneously injecting MSG 2 g/kg BW. Extraction was carried out using the maceration method 96% ethanol. The test parameters observed were body weight, food intake, stool consistency and weight, liver and abdominal fat tissue weight. The results showed that high carbohydrate food and monosodium glutamate could induce obesity. Ethanol extract of rose apple leaves at doses of 25, 50, and 100 mg/kg BW body weight had antiobesity activity by inhibiting body weight gain significantly compared to a positive control group (p<0.05). The highest antiobesity effect was shown by the ethanol extract of rose apple leaves at doses of 50 mg/kg BW with % inhibition of body weight gain of 169.3% to a positive control group. Ethanol extract of rose apple leaves may reduce appetite but didn’t have a laxative effect and couldn’t reduce fat deposits in the liver and abdominal fat tissue.